Toxicity of Pexacerfont, a Corticotropin-Releasing Factor Type 1 Receptor Antagonist, in Rats and Dogs. (March 2019) - White, Melvin R.; Graziano, Michael J.; Sanderson, Thomas P.
Pexacerfont is a corticotropin-releasing factor subtype 1 receptor antagonist that was developed for the treatment of anxiety- and stress-related disorders. This report describes the results of repeat-dose oral toxicity studies in rats (3 and 6 months) and dogs (3 months and 1 year). Pexacerfont was well tolerated in all of these studies at exposures equal to or greater than areas under the curve in humans (clinical dose of 100 mg). Microscopic changes in the liver (hepatocellular hypertrophy), thyroid glands (hypertrophy/hyperplasia and adenomas of follicular cells), and pituitary (hypertrophy/hyperplasia and vacuolation of thyrotrophs) were only observed in rats and were considered adaptive changes in response to hepatic enzyme induction and subsequent alterations in serum thyroid hormone levels. Evidence for hepatic enzyme induction in dogs was limited to increased liver weights and reduced thyroxine (T4 ) levels. Mammary gland hyperplasia and altered female estrous cycling were only observed in rats, whereas adverse testicular effects (consistent with minimal to moderate degeneration of the germinal epithelium) were only noted following chronic dosing in dogs. The testicular effects were reversible changes with exposure margins of 8× at the no observed adverse effect level. It is not clear whether the changes in mammary gland, estrous cycling, and testes represent secondary hormonal changes due to perturbation of the hypothalamic–pituitary–adrenal axis or are off-target effects. In conclusion, the results of chronic toxicity studies in rats and dogs show that pexacerfont has an acceptable safety profile to support further clinical testing.